Uncertainty over implications of placental histopathological findings: A survey of Australian and New Zealand neonatologists. (1st October 2019) - Lieschke, Anna; Dahlstrom, Jane E; Kent, Alison L; Sethna, Farah
Abstract : Aim: Placental examination is known to provide useful information following an adverse pregnancy outcome. Despite existing literature and guidelines for placental examination; current workplace practices, attitudes towards the value of placental examination and the knowledge of perinatal clinicians regarding placental lesions of significance are unknown. The aim of the study is to explore the current knowledge of neonatologists and maternal fetal medicine specialists on placental histopathological findings and clinical management based on placental pathology. Methods: A total of 280 specialists working in perinatal centres across Australia and New Zealand were invited to complete a 20‐question online multiple‐choice‐based survey addressing work‐place placental examination practices, and participant beliefs regarding the utility of histopathological findings and follow‐up practices. Results: A total of 74 neonatologists participated in the survey (28.2% response rate). Maternal fetal medicine specialists were excluded due to low response rate (2%). A total of 100% of respondents believed placental examination provided useful information regarding recent pregnancy and neonatal outcomes. They reported being aware of the presence of protocols for macroscopic examination of, and indications for histopathological examination of the placenta (55.4 and 54.1%, respectively). Nine neonatologists reported a system for actioning abnormal placental reports. There was no consensus amongst neonatologists as to which specific placental lesions held implications for future pregnancy or neonatal outcomes, and how these findings should be followed. Conclusions: Our findings show placental examination is valued amongst neonatologists in Australia and New Zealand, but highlights the need for better education regarding the significance and utility of the results and what would be best practice for following up reports.